Validation of the Dynamic Direct Exposure Method for Toxicity Testing of Diesel Exhaust In Vitro. (5th August 2013) - Joeng, Lucky; Hayes, Amanda; Bakand, Shahnaz
Abstract : Diesel exhaust emission is a major health concern because of the complex nature of its gaseous content (e.g., NO2, NO, CO, and CO2 ) and high concentration of particulate matter (PM) less than 2.5 μ m which allows for deeper penetration into the human pulmonary system upon inhalation. The aim of this research was to elucidate the potential toxic effects of diesel exhaust on a human pulmonary-based cellular system. Validation of a dynamic direct exposure method for both laboratory (230 hp Volvo truck engine) and field (Volkswagen Passat passenger car) diesel engines, at idle mode, was implemented. Human pulmonary type II epithelial cells (A549) grown on porous membranes were exposed to unmodified diesel exhaust at a low flow rate (37.5 mL/min). In parallel, diesel emission sampling was also conducted using real-time air monitoring techniques. Induced cellular effects were assessed using a range of in vitro cytotoxicity assays (MTS, ATP, and NRU). Reduction of cell viability was observed in a time-dependent manner following 30–60 mins of exposure with NRU as the most sensitive assay. The results suggest that the dynamic direct exposure method has the potential to be implemented for both laboratory- and field-based in vitro toxicity studies of diesel exhaust emissions.